Advancing early relational health: a collaborative exploration of a research agenda - Dumitriu, Dani; Lavallée, Andréane; Riggs, Jessica L.; Frosch, Cynthia A.; Barker, Tyson V.; Best, Debra L.; Blasingame, Brenda; Bushar, Jessica; Charlot-Swilley, Dominique; Erickson, Elizabeth; Finkel, Morgan A.; Fortune, Bryn; et al. (Frontiers in Pediatrics, 2023)
Here, we introduce the Early Relational Health (ERH) Learning Community's bold, large-scale, collaborative, data-driven and practice-informed research agenda focused on furthering our mechanistic understanding of ERH and identifying feasible and effective practices for making ERH promotion a routine and integrated component of pediatric primary care. The ERH Learning Community, formed by a team of parent/caregiver leaders, pediatric care clinicians, researchers, and early childhood development specialists, is a workgroup of Nurture Connection -a hub geared toward promoting ERH, i.e., the positive and nurturing relationship between young children and their parent(s)/caregiver(s), in families and communities nationwide. In response to the current child mental health crisis and the American Academy of Pediatrics (AAP) policy statement promoting ERH, the ERH Learning Community held an in-person meeting at the AAP national headquarters in December 2022 where members collaboratively designed an integrated research agenda to advance ERH. This agenda weaves together community partners, clinicians, and academics, melding the principles of participatory engagement and humancentered design, such as early engagement, co-design, iterative feedback, and cultural humility. Here, we present gaps in the ERH literature that prompted this initiative and the co-design activity that led to this novel and iterative community-focused research agenda, with parents/caregivers at the core, and in close collaboration with pediatric clinicians for real-world promotion of ERH in the pediatric primary care setting.